1984
DOI: 10.1002/ange.19840961109
|View full text |Cite
|
Sign up to set email alerts
|

Konformation von Glycosyl‐Radikalen: Radikalstabilisierung durch β‐CO‐Bindungen

Abstract: FeMo-Cofaktor aus Azobacter vinelandii e n t s p r i~h t~~. ~~ (vgl. auch [' I). Die Synthese von 1 ist somit wahrscheinlich ein wesentlicher Schritt in Richtung einer Verbindung, die in diesem Zusammenhang als Modellsubstanz bezeichnet werden kann. Arbeitsvorschr.@Alle Arbeiten werden unter Stickstoff in wasser-und sauerstofffreien uisungsmitteln ausgefiihrt. 0.06 g (1.07 mmol) Fe, 0.13 g (0.52 mmol) E 4 N I und 0.07 g (0.27 mmol) I2 werden in 60 mL CHICll 24 h bei Raumtemperatur geriihrt. Nach Zugabe von 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The only dynamic EPR measurements reported previously were of unsubstituted or mono-substituted rings. [10][11][12][13][14][15] While Kemp's triacid itself favors equatorial methyl groups and axial acid moieties, in the triply deprotonated structure (above pH 9), Coulombic repulsion forces the methyl groups axial so that the charged carboxylates can be as far apart as possible in the equatorial position. 6 Our computational results, described in detail below, support the hypothesis that the KTA and CTA radicals are rigidly locked in one chair conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only dynamic EPR measurements reported previously were of unsubstituted or mono-substituted rings. [10][11][12][13][14][15] While Kemp's triacid itself favors equatorial methyl groups and axial acid moieties, in the triply deprotonated structure (above pH 9), Coulombic repulsion forces the methyl groups axial so that the charged carboxylates can be as far apart as possible in the equatorial position. 6 Our computational results, described in detail below, support the hypothesis that the KTA and CTA radicals are rigidly locked in one chair conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The conformational dynamics of heterocyclic radicals from sugars have been studied in great detail, by Giese in particular. However, reports of EPR parameters for heavily substituted cyclohexyl radicals (with only carbon atoms in the ring) in the literature are sparse, particularly those with doubly substituted ring carbons. These are interesting structures whose solution chemistry and spectroscopy have not been studied extensively to date, yet they are expected to have a rich chemistry in terms of the reactions that produce them, their possible rearrangements to other radicals, and the products they can form.…”
Section: Introductionmentioning
confidence: 99%
“…(1)] and the detection of carbonbased radicals in time-resolved EPR measurements after pulsed irradiation of the reaction mixture. [9,15] Based on these observations, we propose Scheme 2 as a plausible mechanism. ET from photogenerated [Ru II (bpy) 3 ] + to glycosyl bromide generates the C1 radical, which can be reduced (k 1 ) or added to the alkene (k 2 ); for electron deficient alkenes k 2 > k 1 .…”
mentioning
confidence: 94%
“…Stephenson recently demonstrated that electrophilic radicals could be generated in this fashion and intramolecularly trapped in a cascade process. [8] We report herein that the combination of visible light and [Ru(bpy) 3 ] 2+ yields nucleophilic C1 sugar radicals [9] that react intermolecularly with electron-deficient alkenes to provide C-glycosides in yields approaching or exceeding previous bests and with outstanding C1 diastereoselectivites.…”
mentioning
confidence: 99%
“…The observed a-selectivity can be attributed to the kinetic anomeric effect. [35,36] The mannopyranosyl radical intermediate adapts a chair-like conformation 61, [37] stabilized by the hyperconjugation of the nonbonding orbital of the ring oxygen, the radical orbital (SOMO), and the s* orbital of the adjacent C2 À O bond. The attack of the nickel intermediate to the mannopyranosyl radical favors the axial direction because the transition state can be stabilized by the donation of the nonbonding electron pairs on the ring oxygen to the antibonding orbital (s*°) of the newly formed C1-Ni s-bond.…”
mentioning
confidence: 99%